A strategic approach to improving the efficiency of socio-economic activities of consumer cooperation - Мілька, Алла Іванівна (Technology audit and production reserves, 2015)
Strategic approach to the development of measures to improve the efficiency of socio-economic activities of organizations and enterprises of consumer cooperation based on an adapted balanced scorecard is proposed in the article. The urgency of the problem, lack of elaborated theoretical and methodological framework applied to ensure the effectiveness of socio-economic activities of enterprises and organizations, including the system of consumer cooperatives, have necessitated more detailed study of the problem, which is the purpose of researching this article. The study suggested for organizations and enterprises of consumer cooperation: the causal relationships between prospects, the relationship system of main elements of the balanced scorecard, strategy maps and matrix to the overall strategy map. The recommendations are proposed to improve the efficiency of socio-economic activities of organizations and enterprises of consumer cooperation based on a balanced scorecard designed for online analytical information about the effectiveness of management, level of implementation of the main objectives in all areas of activity. Calculation of key indicators in key areas of organizations and enterprises of consumer cooperation would allow the evaluation of the management system of these enterprises, identify its weaknesses and their timely elimination.